Psychometric properties of graduate employability instrument among Malaysian higher education institution students - Roslan, Samsilah; Wong, Siew Ping; Sulaiman, Tajularipin; Ab. Jalil, Habibah; Siaw, Yan Li (Horizon Research Publishing, 2020)
Sustainable Development Goals defined that quality education and youth employment are two inter-related indicators that reflect the economic growth. It is important to conduct early assessment of graduate employability to better equip them with necessary knowledge and skills to increase their chance of achieving more sustainable future in their career path. This study aims to develop and validate an instrument termed as the Graduate Employability Instrument to measure the employability attributes among the undergraduate students. This involved five stages of scale development. The technical analyses are done according to the accepted standards in psychometric testing comprising exploratory factor analysis, reliability analysis and confirmatory factor analyses. Total 425 Malaysian undergraduate students were involved in the study. The findings supported the main proposed model with 33 items grouped in 7 constructs; work and career resilience, human and social capital, teamwork, conscientiousness, critical thinking, academic, and leadership. This study contributed in measuring self-perceived employability of undergraduate students, which reflected the dimensions of strengths in the higher education institution studied towards preparing youth to fit in the competitive working environment. This can be used for continuous programmer improvements and intervention plans to improve the quality of education and resolve youth unemployment issues.